The Information-Gathering Matrix: A Framework for Conceptualizing the Use of Freedom of Information Laws. Issue 4 (April 2018) - Michener, Gregory; Worthy, Ben
Scholarship on transparency and freedom of information (FOI) conveys an overwhelmingly "political" narrative. Most uses of FOI, however, are private and nonpolitical in nature. This article explores the gap between the literature and empirical reality by means of an "Information-Gathering Matrix, " a framework for conceptualizing the motivations, uses, and impacts associated with FOI. Following a broad literature review, case studies illustrate that while FOI uses may be multifarious and prima facie nonpolitical, at least three of the matrix's four quadrants—from the public to the private and the political to the nonpolitical—frequently tend toward politicization.